Highly Flexible Fabrics/Epoxy Composites with Hybrid Carbon Nanofillers for Absorption-Dominated Electromagnetic Interference Shielding - Jong-Hoon Lee; Yoon-Sub Kim; Hea-Jin Ru; Seul-Yi Lee; Soo-Jin Park (Nano-Micro Letters, 2022)
Abstract Epoxy-based nanocomposites can be ideal electromagnetic interference (EMI)-shielding materials owing to their lightness, chemical inertness, and mechanical durability. However, poor conductivity and brittleness of the epoxy resin are challenges for fast-growing portable and flexible EMI-shielding applications, such as smart wristband, medical cloth, aerospace, and military equipment. In this study, we explored hybrid nanofillers of single-walled carbon nanotubes (SWCNT)/reduced graphene oxide (rGO) as conductive inks and polyester fabrics (PFs) as a substrate for flexible EMI-shielding composites. The highest electrical conductivity and fracture toughness of the SWCNT/rGO/PF/epoxy composites were 30.2 S m−1 and 38.5 MPa m1/2, which are ~ 270 and 65% enhancement over those of the composites without SWCNTs, respectively. Excellent mechanical durability was demonstrated by stable electrical conductivity retention during 1000 cycles of bending test. An EMI-shielding effectiveness of ~ 41 dB in the X-band frequency of 8.2–12.4 GHz with a thickness of 0.6 mm was obtained with an EM absorption-dominant behavior over a 0.7 absorption coefficient. These results are attributed to the hierarchical architecture of the macroscale PF skeleton and nanoscale SWCNT/rGO networks, leading to superior EMI-shielding performance. We believe that this approach provides highly flexible and robust EMI-shielding composites for next-generation wearable electronic devices.